Exploring an EAP writing teacher's adaptive expertise and adaptive teaching practices from a CDST perspective - Xiang, Xiaoting; Chang, Pengyun; Yu, Baohua (Frontiers in Psychology, 2022)
Teachers’ adaptive expertise (AE) has received more and more attention in current EFL teaching field but a few studied AE with teachers’ adaptive practices during the class. Adopting a mixed-method design, this study was conducted to explore the adaptive teaching features that EAP writing teachers demonstrated in the academic writing course, from a complex dynamic systems theory perspective. Qualitative results confirmed the complexity of an EAP writing teacher’s adaptive teaching practices with the features of non-linearity, interconnectedness and self-organization. Meanwhile, it indicated that the teacher’s adaptive teaching was facilitated by the development of meta-cognitive, cognitive, and affective and social components of AE. The teacher’s adaptive teaching practices would significantly influence EFL learners’ learning motivation and efficiency in a long-run, which were proved by the quantitative and qualitative data collected from EFL learners. Findings of this study pave the way for future studies in researching teacher expertise from a CDST perspective. Moreover, pedagogical contributions are also achieved in class design and development for tertiary EAP writing course.